The calculation of the uncertainty of the orifice-plate discharge coefficient. (December 2021) - Reader-Harris, Michael; Forsyth, Claire; Boussouara, Tariq
Abstract: The uncertainty of the orifice-plate discharge coefficient given by the Reader-Harris/Gallagher (1998) Equation has been calculated taking account of the uncertainty of the data on which it is based and of the variability in manufacture permitted by ISO 5167–2. This work has shown that using the correct method to determine the uncertainty in ISO 5167-2 has made an insignificant difference to the value given in the standard. However, in other similar cases where the uncertainty for an artefact is based on data from other similar artefacts the uncertainty values obtained by the correct method may be significantly different from those by the incorrect method. Highlights: The orifice discharge coefficient equation uncertainty is correctly calculated here. Calculating uncertainty for an artefact based on data from other similar artefacts. The uncertainty of the Reader-Harris/Gallagher (1998) Equation is confirmed.